The German occupation of Poland : extract of note addressed to the governments of the allied and neutral powers on may 3, 1941 - Republic of Poland. Ministry of foreign Affairs (London : The Cornwall Press, 1941)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Wereldoorlog 2; oorlogsmisdaden; Polen